SISTEM SOSIAL BERBURU BABI PADA MASYARAKAT KABUPATEN KUANTAN SINGINGI (Studi Deskriptif Persatuan Olahraga Berburu Babi) - Bayu Gusti Hendri; Indrawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research was conducted in Kabupaten Kuantan Singingi. The aim of this study was to determine what elements are in the social system boar hunting in Kabupaten Kuantan Singingi. This study entitled "Social Systems Society Hunting Pigs in Desa Koto Taluk Kecamatan Kuantan Tengah Kabupaten Kuantan Singingi ". Topics focus of this research are the elements of what is in the social system boar hunting in Kabupaten Kuantan Singingi. Samples from this study is that people desa koto taluk. taking samples was done by simple random sampling technique. Key informants are the elder person in the group boar hunting Koto village Taluk totaling 1. While this research Informants Informants are 5 people consisting of members of the group boar hunting in Kabupaten Kuantan Singingi. The author uses qualitative descriptive method and the data was analyzed qualitatively. Data instrument is observation, interviews, questionnaires and documentation. The results showed that the pig hunt is done in Kuantan Singingi, there are some elements of a social system that was found, that the purpose of hunting pigs, trust and knowledge, and the facilities used. There are four forms of implementation boar hunting game in Kuansing, which Olek Hunting, Hunting Sunday, Tuesday Hunting, Hunting Solek. In the game of hunting there are some functions in society melakuknannya, namely the function of manifest and latent functions, ie functions manifest (Mutual cooperation to combat pests, sport and hobby, Tourism and recreation, social function) b. Latent function (Prsetise function, performance function of wealth, markets function veiled).Keywords: Social System, Social Groups, Pig Hunting Game Function